Evaluating the impact of policy research: Evidence from the evaluation of rural policy research in developing countries - Slade, Roger; Hazell, Peter B. R.; Place, Frank; Renkow, Mitch (SAGE Publications, 2020)
Policy research concerning developing countries must compete for scarce resources with alternative development investments, many of which are amenable to quantitative assessment of their impact and economic efficiency. This is especially true for policy research that addresses agriculture, food and rural poverty—rural policy research. This paper draws on existing evaluations of rural policy research to identify good practice in the conduct of impact evaluations in developing countries. While much has been learnt from these evaluations about how rural policy research can influence policies, the impact of the policy changes that may follow, and about methods for conducting such studies, very few have assessed the efficiency or economic benefit of rural policy research investments. The paper concludes that while the current focus on the use of mixed-method evaluations is necessary and sufficient in most cases, in the context of allocating public resources, evaluations that provide plausible estimates of the rates of return to major rural policy research investments, or even rural policy research institutions yield important additional and comparative information for decision makers. However, such quantitative assessments do not replace but depend on the prior conduct of qualitative and mixed-method evaluations.